2009
DOI: 10.1590/s0044-59672009000100030
|View full text |Cite
|
Sign up to set email alerts
|

Parasitóides (Hymenoptera: Braconidae) de Anastrepha Schiner (Diptera: Tephritidae) no estado do Acre

Abstract: Este trabalho relata a primeira ocorrência de parasitóides em moscas-das-frutas do gênero Anastrepha Schiner no estado do Acre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
3
0
4
Order By: Relevance
“…Em diversos estados do Brasil, D. areolatus é registrado como a espécie mais comum e o principal responsável pelo parasitismo natural de espécies de Anastrepha (BOMFIM et al, 2007;DEUS et al, 2009;JESUS et al, 2008;MARCHIORI et al, 2000;MARINHO et al, 2009;SALLES, 1996;SILVA et al, 2007;SILVA;SILVA, 2007;SOUZA FILHO et al, 2009;THOMAZINI;ALBUQUERQUE, 2009). …”
Section: Introductionunclassified
“…Em diversos estados do Brasil, D. areolatus é registrado como a espécie mais comum e o principal responsável pelo parasitismo natural de espécies de Anastrepha (BOMFIM et al, 2007;DEUS et al, 2009;JESUS et al, 2008;MARCHIORI et al, 2000;MARINHO et al, 2009;SALLES, 1996;SILVA et al, 2007;SILVA;SILVA, 2007;SOUZA FILHO et al, 2009;THOMAZINI;ALBUQUERQUE, 2009). …”
Section: Introductionunclassified
“…Most studies focused on parasitoids of frugivorous insect larvae, e.g., Costa et al (2009) found seven species of Braconidae of the subfamily Alysiinae and three Opiinae in the Adolpho Ducke forest reserve in Manaus. In a similar study, Thomazini & Albuquerque (2009) also reported three species of Opiinae parasitizing the larvae of fruit flies in Acre State. Pereira et al (2010) related the first record of Doryctobracon areolatus (Szépligeti) and Opius bellus Gahan (Opiinae) in the larvae of fruit flies collected in Rondônia.…”
mentioning
confidence: 70%
“…Os índices de infestação foram elevados, uma média de 1,52 pupários/fruto e 183,88 pupários/kg de fruto (Tabela 2). Thomazini & Albuquerque (2009), estudando os parasitoides que ocorrem em cajazeira no Estado do Acre, registraram índices de infestação de 1,7 pupários/fruto e 195 pupários/kg de fruto. Segundo Araújo (2002), o limite mínimo de infestação por moscas-das-frutas para um hospedeiro ser considerado primário é de 30 pupários/kg de fruto, logo, a cajazeira pode ser considerada um hospedeiro primário para A. obliqua na região.…”
Section: Conclusõesunclassified